Obstetric Outcomes: A Comparison of Teenagers and Adults - Adhikari, Home Nath; Sinha, Kavita; Pandey, Aashish (Journal of Nepalgunj Medical College, 2025)
Introduction: Teenage pregnancy poses significant risks to maternal and neonatal health, particularly in low-resource settings like Nepal, where adolescent pregnancies are linked to higher morbidity and mortality. Aims: To compare obstetric outcome between teenage mothers and adult mothers. Methods: A hospital based prospective case-control study was conducted at a tertiary hospital in Nepal over six months, including 94 participants (47 teenagers aged 13–19, 47 adults aged 20–35). Data on antenatal complications, delivery methods, and postpartum outcomes were analyzed using SPSS v 24.0 with Chi-square, independent t-tests, and Fisher’s exact tests. Results: Teenage mothers were predominantly primigravida (87.2% vs. 29.8%, p<0.001) and had higher rates of intrauterine growth restriction (12.8% vs. 2.1%, OR=6.82, p=0.046). Adults exhibited higher cesarean deliveries (40.4% vs. 19.1%, p=0.002) and gestational diabetes (4.3% vs. 0%). Postpartum complications were more frequent in adults (14.9% vs. 6.4%, p=0.189), while teenagers uniquely experienced postpartum eclampsia (2.1%). The second stage of labor was prolonged in teenagers (45.89 vs. 28.75 minutes, p=0.001). Conclusion: Teenage pregnancies are associated with intra uterine growth restriction and prolonged labor, necessitating policies to delay childbearing, improve prenatal care access, and enhance nutritional and educational support for adolescents in community.